One-Stop Integrated Service Policy in Local Government: Insight from the Ministry of Religious Affairs Office in Tarakan City - Likuwatan Werang, Nicolaus Petrus (Journal of Governance Innovation, 2025)
This essay examines the implementation of the One-Stop Integrated Service (PTSP) policy at the Tarakan City Ministry of Religious Affairs Office, focusing on the obstacles to optimizing public services. Furthermore, the researcher uses a qualitative descriptive approach to examine how the PTSP policy is implemented and the obstacles encountered in each stage of the service delivery process. Data are then collected through interviews with key informants involved in the actual implementation of the PTSP policy. The research findings indicate that the implementation of the PTSP policy at the Tarakan City Ministry of Religious Affairs Office has not fully achieved its objectives due to limited human resources, budget constraints, and inadequate infrastructure. Similarly, although the policy has the potential to streamline services, operational obstacles persist, resulting in suboptimal effectiveness and delays in implementation. In summary, this essay confirms that the literature on public policy implementation argues that, although the PTSP policy aims to improve service efficiency, its success depends heavily on basic resources and institutional support.